Plane-wave phase-coherence imaging for NDE. (April 2017) - Cruza, J.F.; Camacho, J.; Fritsch, C.
Abstract: In ultrasound imaging with arrays the frame rate is limited by the number of insonifications of the inspected medium. In the limit, a single omnidirectional or plane wave insonification (OWI or PWI, respectively) would provide the maximum frame rate. However, since focusing is applied in reception only, this method yields a poor image quality (resolution, SNR, sidelobe levels, etc.). By contrast, multi-insonification techniques, such as the Total Focusing Method (TFM) or Multi-Plane Wave Imaging (M-PWI) provide the highest quality images, although they require more acquisition time. This work tries to achieve the image quality of TFM and M-PWI with a single plane-wave insonification to provide ultra-fast imaging at frame rates of tens of KHz. This is achieved by weighting the plane wave image with a phase coherence factor that keeps in-focus indications and suppresses spurious signals. The bases of the new Plane Wave with Phase Coherence Imaging (PWPCI) are described. Experimental work is also carried out to contrast the image quality with that provided by the well established gold standard TFM. This work demonstrates that the proposed PWPCI technique provides similar or superior image quality than TFM at significantly higher frame rates. Highlights: Ultrafast imaging capability in NDE achieving thousands of images/s. High imaging quality competing with that of the gold standard TFM. Beamforming and processing of a single Plane Wave emission with phase coherence. Improved dynamic range over TFM with a reduced number (3) of plane wave emissions. Theory and experimental verification of Plane Wave Phase Coherent Imaging (PWPCI).